Direct‐Writing of 2D Diodes by Focused Ion Beams (Adv. Funct. Mater. 34/2021). (20th August 2021) - Liu, Yanran; Qu, Yuanyuan; Liu, Yue; Yin, Hang; Liu, Jinglun; Tan, Yang; Chen, Feng
Abstract : Focused Ion Beam Writing In article number 2102708, Yang Tan, Feng Chen, and co‐workers present a new method to "print" lateral PN junctions in MoSe2 /graphene bilayers via ion beam irradiation. Controllable, focused Ga + ions generate Se‐defects on the top of the heterostructures and yield unique electronic properties. This work presents focused ions as an additional strategy for the direct‐writing of elementary electronic devices in 2D materials.